Sulla legge belga che ha esteso anche ai minori (che si trovano in particolari condizioni) il diritto di morire (TEST BioLaw Journal - Rivista di BioDiritto, 2014)
The Authors discuss the recent Belgian law, that extends the category of persons entitled to require euthanasia, including all under age persons, differently than Dutch law. In particular, the Authors examine the precautionary and procedural obligations of the Belgian law, before neutrally assessing its guiding principles. Guiding principles that constitute an important stimulating factor for medical community, that must indicate which modern multi?axial instruments can explore the “decisionmaking capacity” of under age person, especially in order not to confuse it with the legal competence.
Keywords: Belgium; right to die; minors; selfâ€determination; decision making capacity